2020
DOI: 10.1088/1757-899x/850/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Small Vessel Tracking Based on Multi Gateway LORA for Indramayu Traditional Fishery

Abstract: In this study, we use Lora-based data communication for communication between boats and database management systems for vessel. The maximum distance from the Lora is 10 km, and in order to be able to monitor fishermen along the fisherman’s coast in fishing, it is necessary to have a multi-gateway Lora to increase fishermen’s tracking coverage. The system is built using multi gateway Lora installed on the coast. Devices built with a Lora client are installed on a boat with GPS input, the technique of sending da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Fishing is the main livelihood for almost all Indonesian coast people [19], at <5 gross tonnage (GT), with the fishermen observed to only carry out one-day activity [20]. This showed that the use of long-distance wireless communication technology greatly assisted small vessel clients to increase their productivity and safety.…”
Section: Another Back-end Menumentioning
confidence: 99%
“…Fishing is the main livelihood for almost all Indonesian coast people [19], at <5 gross tonnage (GT), with the fishermen observed to only carry out one-day activity [20]. This showed that the use of long-distance wireless communication technology greatly assisted small vessel clients to increase their productivity and safety.…”
Section: Another Back-end Menumentioning
confidence: 99%
“…These factors emphasize the need for alternate solutions that offer greater efficiency, such as systems built on LoRa technology. Recently, a large number of studies have focused on the capabilities and limitations of LoRaWAN multi-gateway [9][10][11][12][13]. In [9], the scalability of LoRa communication for multimode can be improved by collaborating gateways.…”
Section: Introductionmentioning
confidence: 99%
“…In [9], the scalability of LoRa communication for multimode can be improved by collaborating gateways. The implementation of vessel tracking utilizing multiple gateways was carried out as described in [10]. The outcome of this research was the successful development of a vessel monitoring system that provided extensive coverage for fishing boats along the coast.…”
Section: Introductionmentioning
confidence: 99%